Control architecture and design method of reconfigurable manufacturing systems. (April 2016) - da Silva, Robson Marinho; Junqueira, Fabrício; Filho, Diolino J. Santos; Miyagi, Paulo E.
Abstract: This paper proposes a control architecture for reconfigurable manufacturing systems and its design method based on Petri nets (Input Output Place Transition and Production Flow Schema), Service-Oriented Architecture and Holonic and Multi-Agent System techniques, among other good practices. The control architecture integrates value-added activities, information and resources. The method considers the exchange of knowledge among heterogeneous business workflow of manufacturing subsystems in different geographical locations, and allows modeling process, product, machine and device control. An example demonstrates advantages of the resulting control system. Abstract : Graphical abstract: Abstract : Highlights: A control architecture for reconfigurable manufacturing systems and its design method are proposed. The proposal is based on PN, SOA and HMAS techniques and other good practices. Resulting control system considers reconfiguration in functionality and in production capacity.